1992
DOI: 10.1111/j.1532-849x.1992.tb00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Labial Margin Design on Stress Distribution of a Porcelain‐Fused‐to‐Metal Crown

Abstract: The change of cement thickness of the chamfer margin is significantly greater than that of either the rounded-shoulder or the bevelled-shoulder margin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Farah and Craig20 studied 3 marginal configurations (chamfer, chisel, and shoulder with a bevel) with no cement interface and suggested that the chamfer configuration exhibited the most uniform stress distribution. Another study21 evaluated the effects of labial margin design on stress distribution of metal‐ceramic crowns, and no differences were found at the cement‐dentin and metal‐cement interface of 3 different margin configurations (chamfer, rounded shoulder with knife‐edge metal finish, rounded shoulder with beveled metal finish). No differences were found for axial stresses, whereas the differences in radial stresses were of questionable clinical value according to those authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farah and Craig20 studied 3 marginal configurations (chamfer, chisel, and shoulder with a bevel) with no cement interface and suggested that the chamfer configuration exhibited the most uniform stress distribution. Another study21 evaluated the effects of labial margin design on stress distribution of metal‐ceramic crowns, and no differences were found at the cement‐dentin and metal‐cement interface of 3 different margin configurations (chamfer, rounded shoulder with knife‐edge metal finish, rounded shoulder with beveled metal finish). No differences were found for axial stresses, whereas the differences in radial stresses were of questionable clinical value according to those authors.…”
Section: Discussionmentioning
confidence: 99%
“…The multitude of factors affecting microleakage under artificial crowns makes the situation complicated and expensive for clinical trials 12. Two‐dimensional finite element analysis (FEA) studies on crowns exist that considered the presence of a cement layer 13–15. In an FEA study that considered the effect of occlusal stresses on the stress distribution in the luting agent beneath full coverage crowns, masticatory loads caused stresses well below the elastic limit of cement.…”
mentioning
confidence: 99%
“…FEA has been used as an alternative tool in biomechanics research. In dentistry, several previous studies used FEA to determine how geometry, loading, material properties, and stress distribution influence dental restoration survival . The risk of failure in restorations can be quantified by dividing the maximum stress of the restoration design by the strength of the material.…”
Section: Introductionmentioning
confidence: 99%
“…In dentistry, several previous studies used FEA to determine how geometry, loading, material properties, and stress distribution influence dental restoration survival. [35][36][37][38][39] The risk of failure in restorations can be quantified by dividing the maximum stress of the restoration design by the strength of the material. Relative safety factor is defined as an inverse of the risk of failure.…”
Section: Introductionmentioning
confidence: 99%
“…12 Two-dimensional finite element analysis (FEA) studies on crowns exist that considered the presence of a cement layer. [13][14][15] In an FEA study that considered the effect of occlusal stresses on the stress distribution in the luting agent beneath full coverage crowns, masticatory loads caused stresses well below the elastic limit of cement. More advanced computer modeling techniques allow careful threedimensional manipulation of clinical variables that could relate to cement microfracture.…”
mentioning
confidence: 99%